Interdisciplinary Perspectives and Approaches in Theologizing in Asia - Daniel Franklin E. Pilario (International Journal of Indonesian Philosophy & Theology, 2020)
This article attempts to answer the question how interdisciplinary is theology in the Asian context? It tackles the issue in three distinct parts: (1) the notion of interdisciplinarity; (2) the relationship between theology and other disciplines; and (3) the principles and practices of interdisciplinary theologizing in Asia. First, interdisciplinarity feeds on the concept of scientific disciplinarity. Though “disciplines” as domains of knowledge exist from the Greeks to the scholastics, disciplinary specialization is a modern creation. The subsequent scientific compartmentalization longed for a synthesis, thus, leading to the varied ways of relating among scientific disciplines expressed in terms like interdisciplinarity, multidisciplinarity and transdisciplinarity. The second part of the article maps how theology has dealt with its “other” throughout history. The third section argues for the dialogical character of both Asian cultures and Asian Christianities. Finding themselves in a land characterized by plural philosophies and religions, it cannot exist but be in dialogue with others. In the Asian continent, the serenity of the lotus meets the defiance of the cross bringing out a theology that expresses both harmony and prophecy, equilibrium and transformation. The article ends by showing methodological principles, theological methods, present practitioners and emerging questions generated by this complex interdisciplinary interaction on the Asian soil. AbstrakArtikel ini berusaha menjawab pertanyaan bagaimana teologi interdisipliner dijalankan dalam konteks Asia? Ada tiga isu yang digarap: (1) makna interdisiplinaritas; (2) keterpautan antara teologi dan disiplin lain; (3) prinsip dan praksis berteologi interdisipliner di Asia. Bagian pertama menggali interdisiplinaritas dalam ilmu-ilmu. Keanekaragaman ilmu-ilmu disimak mulai dari periode filsafat Yunani hingga Skolastik. Ilmu-ilmu modern mendistingsi “keilmiahan” dalam interdisiplinaritas, multidisiplinaritas, dan transdisiplinaritas. Bagian kedua membahas bagaimana teologi mengurus “yang lain” dalam sejarah. Bagian ketiga berargumentasi terkait dengan karakter dialogal dari keduanya, yaitu baik kultur Asia maupun Kekristenan Asia. Karena mendarat di tanah yang bercirikan filsafat dan kebudayaan yang beraneka macam, Kekristenan Asia tidak mungkin melepaskan diri dari dialog dengan yang lain. Di benua Asia, kedamaian lotus berjumpa dengan penebusan salib yang produknya mengukir harmoni dan kritisi, keseimbangan dan transformasi. Artikel berakhir dengan prinsip-prinsip metodologis, metode teologis dari para praktisi saat ini, dan pertanyaan-pertanyaan penting yang muncul dari interaksi interdisipliner yang kompleks di tanah Asia.